What is said, what is silenced, what is obscured: The Report of the Commission on the Social Determinants of Health - José Carlos Escudero (Social Medicine Publication Group, 2024)
The final report of the WHO Commission on Social Determinants of Health (CSDH), chaired by Dr. Marmot of the United Kingdom, is a remarkable document for what it states, what it silences, what it obscures, what actions it advocates, and what it leaves out. A brief analysis of the Commission´ s statements is presented here. The Report is an important landmark in the history of the social determinants of health and in the trajectory of the WHO, the institution which convened the Commission. For WHO, the report represents an auspicious and welcome change in a regrettable trend; since the 1980's WHO has abandoned the ideology of its founders, i.e. an interventionist commitment to improve the situation of poor individuals and countries. The early WHO was a strange and contradictory - yet creative - combination of Social and Christian democracies, of Third World activism promoted by countries in the midst of independence or liberation struggles, and of Eastern European Marxism. All of this was perfectly in sync with the role that the United Nations and its agencies played during the Cold War. With the two rival blocks constantly at odds, there existed a fertile middle ground on which initiatives could develop which promoted social justice and which, in turn, provided legitimacy to the rival Cold Warriors who profited from them. After the disappearance of "really existing" Socialism, triumphant Western neoliberalism began harassing any country which attempted progressive social measures, a harassment that sometimes involved the use of force. WHO and its sister agencies of the UN became the new acolytes of neoliberalism triumphant. WHO gave up its leading role in the world's collective health, and resignedly limited itself to following policies which were designed and implemented by organizations of a neoliberal bent, such as the IMF, the World Bank and the WTO. While the consequences of these policies were not all that clear at the time they were being implemented, their results are clear for all to see: a setback for the concept of health as a social right and a weakening of nation states or communities which prevents them from playing an active role as either service provider or as regulators of the workings of the market. According to neoliberal dogma, the market is the perfect allocator of resources and the ideal arbiter of priorities and policies. Beginning in the unfortunate decade of the 80's, the market, in both general society and in health, weakened labor, increased unemployment , dismantled universal social coverage, lowered salaries, reduced public health expenditures, privatized services, mandated user fees, and decreased supervision of private health care providers and of the pharmaceutical industry. All these initiatives deteriorated the collective physical health. As to mental health, the replacement of more or less predictable individual lives with the uncertainties and unpredictability of unchecked market forces quite clearly deteriorated it. Unfortunately many of these assaults on mental health will never be well recorded since they are largely unquantifiable.